Ferroelectricity in undoped-HfO2 thin films induced by deposition temperature control during atomic layer deposition. Issue 28 (4th July 2016) - Kim, K. D.; Park, M. H.; Kim, H. J.; Kim, Y. J.; Moon, T.; Lee, Y. H.; Hyun, S. D.; Gwon, T.; Hwang, C. S.
Abstract : The evolution of ferroelectricity in undoped-HfO2 thin films is systematically studied by controlling the deposition temperature during atomic layer deposition. Abstract : HfO2 thin films, extensively studied as high- k gate dielectric layers in metal-oxide-semiconductor field effect transistors, have attracted interest of late due to their newly discovered ferroelectricity in doped HfO2 . The appearance of the ferroelectric orthorhombic phase of HfO2 was previously examined in variously doped and undoped systems, but the effects of process-variable changes on the physical and chemical characteristics of a thin film and the resulting ferroelectricity have not been studied systematically. Here, the evolution of ferroelectricity in HfO2 thin films through deposition temperature control during atomic layer deposition was systematically examined without the intentional doping of metallic elements other than Hf. The lower-temperature-deposited HfO2 showed an increased impurity concentration, which was mainly carbon, and the involvement of these impurities suppressed the lateral grain growth during the crystallization thermal treatment. The grain size reduction could stabilize the metastable orthorhombic phase, whose surface and grain boundary energies are lower than those of the room-temperature-stable monoclinic phase, by increasing the grain boundary areas. The 9 nm-thick HfO2 thin film deposited at 220 °C exhibited a remanent polarization value of 10.4 μC cm −2 and endured up to 10 8 switching cycles, which is a 10 2 -fold improvement compared to the previously reported undoped 6 nm-thick HfO2 . This can be ascribed to the decrease in the relative portion of defective interfacial layers by increasing the total film thickness. The strategy of using deposition temperature control is a feasible method for the fabrication of these new lead-free binary ferroelectric thin films.